Ultrasound Combined With Microbubbles Loading BDNF Retrovirus to Open Blood-Brain Barrier for Treatment of Alzheimer's Disease - Feng Wang; Feng Wang; Xi-Xi Wei; Lian-Sheng Chang; Lei Dong; Yong-Ling Wang; Na-Na Li (Frontiers Media S.A., 2021)
Background: Brain-derived nerve growth factor (BDNF) is a promising effective target for the treatment of Alzheimer's disease (AD). BDNF, which has a high molecular weight, has difficulty in crossing the blood-brain barrier (BBB). The study aimed to prepare microbubbles loading brain-derived nerve growth factor (BDNF) retrovirus (MpLXSN-BDNF), to verify the characteristics of the microbubbles, and to study the therapeutic effect of the microbubbles combined with ultrasound on the opening of the blood-brain barrier in an AD rat model.Methods: 32 adult male SD rats were randomly divided into four groups: control group, ultrasound + pLXSN-EGFP microbubble group (U + MpLXSN-BDNF), ultrasound + pLXSN-BDNF microbubble group, and ultrasound + microbubble + pLXSN-BDNF virus group (U + MpLXSN-BDNF), with eight rats in each group. At the same time, the left hippocampus of rats was irradiated with low-frequency focused ultrasound guided by MRI to open the blood-brain barrier (BBB). The effects of BDNF overexpression on AD rats were evaluated behaviorally before and 1 month after the treatment. The number of acetylcholinesterase (ChAT)-positive cells and the content of acetylcholine (ACh) in brain tissues were determined by immunohistochemistry and high-performance liquid chromatography (HPLC), respectively. IF staining of synaptic spines and Western blot of synaptophysin presented herein detected synaptic density recovery.Results: Signal intensity enhancement at the BBB disruption sites could be observed on the MR images. The behavioral evaluation showed that the times of crossing the original platform in the U + MpLXSN-BDNF group increased significantly after treatment. Immunohistochemistry and HPLC revealed that the number of ChAT-positive neurons and the contents of ACh in the brain were significantly decreased in the treated groups compared with the controls. IF staining of synaptic spines and Western blot data of synaptophysin showed that the U + MpLXSN-BDNF group can recover the synaptic loss better by BDNF supplementation than the other treatment groups.Conclusion: Ultrasound combined with viral microbubbles carrying BDNF can increase the transfection efficiency of brain neurons, promote the high expression of exogenous gene BDNF, and play a therapeutic role in the AD model rats.